The acquisition of French as a second language : new developmental perspectives - Lindqvist, Christina; Bardel, Camilla (Benjamins current topics ;, 2014)
It has been argued that the study of child L2 development can inform different maturational accounts of language acquisition. One such specific proposal was put forward by Meisel (2008), arguing for a cut-off point for monolingual or bilingual first language acquisition - (2)L1 - type of development at 3-4 years. The paper analyses the longitudinal development of object clitics in child L2 French (L1 Swedish) and compares the developmental sequence in child L2 learners (n?=?7) with different Ages of onset of Acquisition (AoA) (from 3;0 to 6;5) to the adult L2 sequence that was found in previou.